The long-term impact of the COVID-19 pandemic on physical fitness in young adults: a historical control study - Ripley-Gonzalez, Jeffrey W.; Zhou, Nanjiang; Zeng, Tanghao; You, Baiyang; Zhang, Wenliang; Liu, Jie; Dong, Yuchen; Guo, Ying; Dun, Yaoshan; Liu, Suixin (Scientific reports, 2023)
The strength of evidence regarding long-term changes to fitness resulting from the coronavirus disease 2019 (COVID-19) lockdowns is deficient. This two-site retrospective study aimed to investigate the long-term changes in physical fitness among young adults a year after the onset of the pandemic using a robust historical control. University freshmen who underwent physical fitness tests in 2019 and completed a follow-up in 2020 (study group) were included. The primary focus was to compare the current cohort with a historical control group who completed the same tests a year prior (2018). A total of 5376 individuals were recruited, of which 2239 were in the study group. Compared with the control, the study group exhibited a decrease in anaerobic fitness, with an overall difference of −0.84 (95% confidence interval [CI], [−1.33 to −0.36]); declines in aerobic fitness, with a difference of −2.25 [−3.92 to −0.57] for males and −4.28 [−4.97 to −3.59] for females; a reduced explosive fitness (−2.68 [−3.24 to −2.12]); and a decreased upper-body strength in females (−1.52 [−2.16 to −0.87]). The fitness of young adults has been considerably compromised by COVID-19 lockdowns, highlighting the importance of promoting physical activity to prevent long-term health implications.